Pembelajaran Bahasa Daerah (Jawa) Secara Daring dengan Menerapkan Penggunaan Google Classroom - Utami, Sri (FKIP Universitas Wisnuwardhana, 2022)
E-learning which is an electronic media used as a learning medium can certainly facilitate the implementation of online learning. E-learning provides an easy-to-use method, namely the Google Classroom application, which is an application and can provide online classes. With the Google Classroom application, students / students can easily learn anywhere. As is the case at this time where the COVID-19 pandemic is still not over and must carry out teaching and learning activities through distance learning, an online system is needed. which is also useful as a learning tool in Javanese language subjects. The approach is descriptive qualitative. Meanwhile, the data collection used in this research is in the form of observation, interviews and documentation. To analyze the researchers did namely; collecting data, reducing data, providing data, which then makes conclusions and data validity. To strengthen the data, the researchers conducted data verification using triangulation techniques (synthesis of truth). In this study, it resulted in a response that by implementing the use of online applications (google classroom) that could be affordable in its implementation online during this pandemic. The implementation of Javanese language learning using the Google Classroom application is a fact that makes it easier to find material even though it has been previously conveyed by educators/teachers. The collection of practice questions and assignments through the Google Classroom application is considered safe by students / students, because these exercises and assignments can be stored directly in Google Drive. Even so, the implementation of Javanese language learning using the Google Classroom application still has its drawbacks. The shortcoming lies in students who feel unable to concentrate on learning caused by external disturbances, for example, in this case, noise. Other external disturbances can be in the form of an internet signal when the weather is bad, or the amount of internet credit that he does not have. In this case, in the implementation of Javanese language learning with these obstacles, educators/teachers can provide direction to students/students about solving the problem (solosinya).